Vegetius epitome of military science - Vegetius Renatus, Flavius (Translated texts for historians, 1993)
The only Latin art of war to survive, Vegetius' Epitome was for long a part of the medieval prince's military education. The core of his proposals, the maintenance of a professional standing army, was revolutionary for medieval Europe, while his theory of deterrence through strength remains the foundation of modern Western defence policy.